Pyrylium Salts: Selective Reagents for the Activation of Primary Amino Groups in Organic Synthesis - Pang, Yue; Moser, Daniel; Cornella, Josep (Synthesis, 2020)
Primary amino groups represent an ubiquitous category of functionalities in synthetic building blocks, drugs, and natural products. Therefore, such functionalities offer themselves as perfect handles for late-stage functionalization, and the development of robust and efficient strategies to transform these groups is highly desirable. Despite the extremely challenging activation of the C–N bond, the past few years have witnessed the rapid development of deaminative transformations using pyrylium salts as activating reagents. In most cases, the pyridinium salts formed were activated by single electron transfer, giving alkyl radicals which were used in a series of transformations via nickel and photoredox catalysis. This short review aims to give an overview to related properties of pyrylium salts, their historical significance, and summarize the recent progress in the field of deaminative transformations using these reagents.1 Introduction2 Pyrylium and Pyridinium Salts2.1 Historical Context2.2 Structure and Reactivity2.3 Pyrylium Synthesis2.4 Historical Context of the Reactivity of Pyridinium Salts3 Recent Progress on Deaminative Transformations of Primary Amino Groups by Pyrylium Salts3.1 Metal-Catalyzed Cross-Couplings3.2 Photoredox Catalysis and Photoinduced Reactions for C–C Bond Constructions3.3 Borylations3.4 SNAr Functionalization of Aminoheterocycles4 Conclusion
Keywords: pyrylium salts; primary amino groups; deaminative transformations; radical chemistry; nickel catalysis; photoredox catalysis